If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(1 + -7y) + -14y = -7 (1 * 3 + -7y * 3) + -14y = -7 (3 + -21y) + -14y = -7 Combine like terms: -21y + -14y = -35y 3 + -35y = -7 Solving 3 + -35y = -7 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -35y = -7 + -3 Combine like terms: 3 + -3 = 0 0 + -35y = -7 + -3 -35y = -7 + -3 Combine like terms: -7 + -3 = -10 -35y = -10 Divide each side by '-35'. y = 0.2857142857 Simplifying y = 0.2857142857
| 2x+3ifx=9 | | 3z=1-z | | -4(-4f-10)=3(2f-4)+2 | | 5(24.2)-32=89 | | f+k=z | | 25+25+2x=180 | | 0.1+0.9=.3-.5y | | 8-2z=10+3z | | 5y^2-9y-8=0 | | 13x+8=1x+92 | | (2b+7)(3b-c+9)= | | 4-6.25x=3.8x | | 20x-4.9x^2=0 | | 2k=-24 | | 2(5y-6)=-2 | | 5-2x+3=-8+2x | | -6y+4=76 | | 20=0.18t^3-2.16t^2+4.86t | | 9x^2+4x-44=0 | | (a-3)(6a+7)= | | 4.3=0.5 | | 5=2t | | 1-5xy^2c-3x^2+c=5xyc-4x+3x^2c | | 16-2x=-8x+10 | | (3x-1)(2x+2)= | | 12x-16=2x+14 | | 10x+3(2x+5)=5 | | 46+4x=6x+76 | | 28-3(4-x)=-2 | | 28-3(4-x)=-2 | | 28-3(4-x)=-2 | | 3x+25=40-17x |